Soliton trapping of dispersive waves in tapered optical fibers. - Travers,JC; Taylor,JR (Opt Lett, 2009)
We show that trapping of dispersive waves by solitons is significantly enhanced in tapered optical fibers as compared with nontapered fibers. For the trapping process to occur, the soliton must be decelerating; in nontapered fiber, the cause of soliton deceleration is Raman self-scattering to spectral regions of lower group velocity. It is shown here that deceleration of the soliton due to the changing group velocities in a tapered optical fiber also enables and enhances the trapping process, independently of Raman gain. This explains the enhanced blue spectral extension observed for supercontinuum generation in tapered optical fibers. This result also indicates that trapping of dispersive waves by solitons will also be possible in fibers or waveguides made from materials with negligible Raman self-scattering.